Internalisasi Nilai- Nilai Karakter Islami Melalui Program Full Day School di SMPIT Az-Zahra Sragen - Khadijah Syifaulinas; Muhammad Wildan Shohib (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
In an effort to overcome various moral problems in the educational environment, this study aims to explain the character values that are internalized, the methods and processes of internalization, as well as the supporting and inhibiting factors of internalization at SMPIT Az-Zahra Sragen. full day school program. In this study, a qualitative approach was used, and this type of research is descriptive. Data were collected through observation, interviews, and documentation with the principal, Islamic Religious Education (PAI) teachers, and students. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. In addition, the validity of the data was tested by combining various sources and techniques. The results of the study showed that religiosity, discipline, responsibility, honesty, courage, and politeness are the character values that are internalized. To achieve the internalization strategy, teachers must show good examples to students, use a personal approach, carry out religious and organizational activities, and consistently supervise students. Supporting factors include school cooperation with the PPTQ team, the role of teachers as examples and guides, student activeness, parental support, and a pleasant school environment. Inhibiting factors include limited school facilities and infrastructure, the influence of the environment outside the school, lack of supervision from students’ homes, and differences in students’ backgrounds. Therefore, the full day school program helps internalize character values consistently.